Hydrogels for Treatment of Different Degrees of Osteoarthritis - Wang, Shuze; Qiu, Yueyang; Qu, Liu; Wang, Qiang; Zhou, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a very common disease that severely restricts people's activities and degrades their quality of life. Every year millions of people worldwide suffer from osteoarthritis, placing a heavy burden on society. As a kind of polymer material with high water content and high regulation, hydrogel provides a new way for the treatment of osteoarthritis. In recent years, with the development of materials science and tissue engineering technology, hydrogel therapy for osteoarthritis has been widely studied. In this paper, the research progress of hydrogel in the treatment of osteoarthritis in recent three years is reviewed. According to the development and treatment of osteoarthritis, we summarized the required hydrogel properties and current applications. This article also presents the challenges of hydrogels for different types of osteoarthritis and describes the prospects for future development.